Bringing the english curriculum to life : a field guide for making meaning in english - Didau, David (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Bringing the English Curriculum to Life builds on David Didau's groundbreaking book Making Meaning in English by showing how the principles of the original book can be applied in schools and classrooms. Drawing together experiences of designing, teaching, supporting and assessing English across the schools within Ormiston Academies Trust, this book demonstrates what an ambitious, coherently sequenced, broad and balanced English curriculum with successful adaption for students with SEND can look like in practice. Designed around the explicit teaching of the powerful conceptual knowledge students need to master the discipline, the book offers a fully resourced English curriculum packed with teaching suggestions and examples of high-quality practice. Covering intent, implementation, assessment, and outlining in detail what is included in each module for KS3 and 4, the curriculum can be adopted in its entirety, but is also flexible enough for departments to take modules and slot them into their own curriculum. Providing an inspiring model for teaching English that enables all students to succeed, this is an essential resource for all English teachers and school leaders responsible for curriculum development"--
Keywords: English language -- Study and teaching (Middle school); English language -- Study and teaching (Secondary); Language arts -- Correlation with content subjects; Language arts -- Curricula; EDUCATION / Secondary; EDUCATION / Leadership; EDUCATION / Professional Development